DAMPAK INTERVENSI ERGONOMI TERHADAP KESEHATAN PEKERJA KANTORAN: TINJAUAN SISTEMATIS DENGAN FOKUS PADA INTERVENSI BERBASIS TEKNOLOGI DAN INTEGRASI KESEJAHTERAAN MENTAL - Meylia Vivi Putri; Dwila Sempi Yusiani (Jurnal Liga Ilmu Serantau, 2025)
This study aims to provide a systematic review of the impact of ergonomic interventions on office workers' health, focusing on technology-based interventions and mental well-being. Office workers who spend long hours in front of computer screens are at high risk of developing musculoskeletal disorders, such as back pain, neck strain, and eye strain, as well as mental health issues such as stress and anxiety. While physical ergonomic interventions, such as adjusting chair, desk, and computer screen positions, have been proven effective in reducing physical complaints, this study also explores the use of advanced technologies such as wearable devices to monitor posture, break reminder apps, and virtual reality (VR) training. Furthermore, mental well-being programs that involve mindfulness and breathing relaxation techniques have been shown to reduce stress levels and improve workers' psychological well-being. The review results indicate that a combination of physical, technology-based, and mental well-being interventions has a significant impact on improving comfort, reducing physical strain, and enhancing mental health and productivity. Therefore, this study recommends that companies integrate these three aspects into their ergonomic policies to create a healthier and more productive work environment.